Pengaruh Fear of Failure terhadap Prokrastinasi Akademik Mahasiswa Skripsi di Kota Bandung - Firania Rohaeni; Farida Coralia (Bandung Conference Series: Psychology Science, 2024)
Abstract. This research aims to identify the effect of fear of failure towards academic procrastination of final-year university students in Bandung city. It utilizes the fear of failure theory by Conroy and academic procrastination by Solomon and Rothblum. It employs a non-experimental quantitative approach using the causality study design to describe the scale of impact of the fear of failure variable towards academic procrastination. The total participants of this study are 334 final-year university students in Bandung. The study uses the Performance Failure Appraisal Inventory (PFAI) arranged and developed by Conroy and adapted by Bauzir for the measurement tool. It also uses the Thesis Writing Procrastination Scale (TW-PS) developed by Diniy Hidayatur Rahman. The result indicates the presence of the effect of fear of failure towards academic procrastination of final year university students in Bandung. The scale of this fear of failure effect towards academic procrastination is low for 18,2%. Abstrak. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh fear of failure terhadap prokrastinasi akademik pada mahasiswa akhir di Kota Bandung. Peneliti menggunakan konsep teori dari Conroy untuk menjelaskan konsep fear of failure dan teori dari Solomon dan Rothblum untuk menjelaskan konsep prokrastinasi akademik. Penelitian ini menggunakan desain studi kausalitas untuk menjelaskan besar pengaruh variabel fear of failure terhadap variabel prokrastinasi akademik. Partisipan dalam penelitian ini berjumlah 334 mahasiswa skripsi di Kota Bandung. Alat ukur yang digunakan pada penelitian ini adalah Performance Failure Appraisal Inventory (PFAI) alat ukur yang disusun dan dikembangkan oleh Conroy dan diadaptasi oleh Bauzir, serta Thesis Writing Procrastination Scale (TW-PS) yang dikembangkan oleh Diniy Hidayatur Rahman. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh fear of failure terhadap prokrastinasi akademik pada mahasiswa skripsi di Kota Bandung. Pengaruh fear of failure terhadap prokrastinasi akademik rendah hanya 18,2%.